(untitled) (Revista Contexto & Educação, 2021)
Two moments have a central role in teacher training: the Supervised Internship and the Undergraduate Final Work. In Rural Education, such formative paths are little explored as to their nature and their ability to reflect the students identity. This article originates from the pedagogical experiences of professors in the context of a Rural Education Undergraduate Course in the areas of knowledge Natural Sciences and Mathematics and aims to discuss the characteristics and nature of the training of Rural Education students having as objects of analysis their productions and experiences in these curricular components, in the perspective of Pedagogy of Alternation. The research is qualitative and uses as empirical material written productions of the final works and internship reports and guided by the authors over the last few years. It is observed that the work, resulting from the peasant way of life, runs through the productions, both in Sciences and in Mathematics. While in Nature Sciences the internships emphasize the possibility of articulating themes external to the curriculum to the canonical contents of Science Teaching, in Mathematics it is the theoretical and methodological trends that express the dialogue with the themes of everyday life in the internships and final works analyzed.